The use of a cartilage decellularized matrix scaffold for the repair of osteochondral defects: the importance of long-term studies in a large animal model - Vindas Bolaños, Rafael (2016)
Objective: To investigate the effect of decellularized cartilage-derived matrix (CDM) scaffolds, by itself and as a composite scaffold with a calcium phosphate (CaP) base, for the repair of osteochondral defects. It was hypothesized that the chondral defects would heal with fibrocartilaginous tissue and that the composite scaffold would result in better bone formation. Methods: After an 8-week pilot experiment in a single horse, scaffolds were implanted in eight healthy horses in osteochondral defects on the medial trochlear ridge of the femur. In one joint a composite CDMeCaP scaffold was implanted (þP), in the contralateral joint a CDM only (P) scaffold. After euthanasia at 6 months, tissues were analysed by histology, immunohistochemistry, micro-CT, biochemistry and biomechanical evaluation. Results: The 8-week pilot showed encouraging formation of bone and cartilage, but incomplete defect filling. At 6 months, micro-CT and histology showed much more limited filling of the defect, but the CaP component of the þP scaffolds was well integrated with the surrounding bone. The repair tissue was fibrotic with high collagen type I and low type II content and with no differences between the groups. There were also no biochemical differences between the groups and repair tissue was much less stiff than normal tissue (P < 0.0001). Conclusions: The implants failed to produce reasonable repair tissue in this osteochondral defect model, although the CaP base in the P group integrated well with the recipient bone. The study stresses the importance of long-term in vivo studies to assess the efficacy of cartilage repair techniques.